1997
DOI: 10.1177/019251397018004003
|View full text |Cite
|
Sign up to set email alerts
|

Gender, High- and Low-Schedule-Control Housework Tasks, and Psychological Distress

Abstract: In this analysis, with data collected from a random sample of 265 employed dual-earner couples, we estimated the association between time spent on housework tasks on one hand and psychological distress on the other. Based on the literature relating job control to mental health outcomes, we hypothesized that hours spent in low-schedule-control tasks, but not total hours spent in housework tasks or hours spent in high-schedule-control tasks, would be associated with psychological distress. Further, we hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
135
3
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 31 publications
9
135
3
1
Order By: Relevance
“…Based on the work of Barnett and Shen [21], housework tasks were further divided into high schedule control tasks (e.g., doing outdoor tasks, paying bills, and maintaining vehicles) and low schedule control tasks (e.g., preparing meals, washing dishes, cleaning house, shopping, and washing and ironing). Thus, two additional measures were constructed: 1) perceived relative time spent in high-schedule-control tasks, and 2) perceived relative time spent in low-schedule-control tasks.…”
Section: Independent Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the work of Barnett and Shen [21], housework tasks were further divided into high schedule control tasks (e.g., doing outdoor tasks, paying bills, and maintaining vehicles) and low schedule control tasks (e.g., preparing meals, washing dishes, cleaning house, shopping, and washing and ironing). Thus, two additional measures were constructed: 1) perceived relative time spent in high-schedule-control tasks, and 2) perceived relative time spent in low-schedule-control tasks.…”
Section: Independent Variablesmentioning
confidence: 99%
“…For example, for women, studies have found greater absolute time spent in family work to be associated with poorer mental health, [12][13][14] better mental health, but only up to a particular threshold of hours [15], and unrelated to mental health [8,16,17]. Similarly, several studies have reported that the more proportionate time women spend in household labor relative to their partner, the greater their depression or psychological distress [15,17,18], whereas others have reported no such relationship [12,[19][20][21]. Although men are less often included as participants in studies of family labour and well-being [18,19,22], men's mental health, on average, is less likely to be associated with the division of family work [8,16,21], though exceptions have been noted [12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations